Virtual healthcare services and digital health technologies deployed during coronavirus disease 2019 (COVID-19) pandemic in South Africa: a systematic review - Mbunge, Elliot; Batani, John; Gaobotse, Goabaone; Muchemwa, Benhildah (Global Health Journal, 2022)
To identify virtual healthcare services and digital health technologies deployed in South Africa during coronavirus disease 2019 (COVID-19) and the challenges associated with their use. To determine the status of digital health utilization during COVID-19 in South Africa, the preferred reporting items for systematic reviews and meta-analyses model was used to perform a systematic and in-depth critical analysis of previously published studies in well-known and trusted online electronic databases using specific search keywords words that are relevant to this study. We selected published peer-reviewed articles available from the onset of COVID-19 to July 2021. Total of 24 articles were included into this study. This study revealed that South Africa adopted digital technologies such as SMS-based solutions, mobile health applications, telemedicine and telehealth, WhatsApp-based systems, artificial intelligence and chatbots and robotics to provide healthcare services during COVID-19 pandemic. These innovative technologies have been used for various purposes including screening infectious and non-infectious diseases, disease surveillance and monitoring, medication and treatment compliance, creating awareness and communication. The study also revealed that teleconsultation and e-prescription, telelaboratory and telepharmacy, teleeducation and teletraining, teledermatology, teleradiology, telecardiology, teleophthalmology, teleneurology, telerehabilitation, teleoncology and telepsychiatry are among virtual healthcare services delivered through digital health technologies during COVID-19 in South Africa. However, these smart digital health technologies face several impediments such as infrastructural and technological barriers, organization and financial barriers, policy and regulatory barriers as well as cultural barriers. Although COVID-19 has invigorated the use of digital health technologies, there are still some shortcomings. The outbreak of pandemics like COVID-19 in the future is not inevitable. Therefore, we recommend increasing community networks in rural areas to bridge the digital divide and the modification of mHealth policy to advocate for the effective use of innovative technologies in healthcare and the development of sustainable strategies for resources mobilization through private-public partnerships as well as joining available international initiatives advocating for smart digital health.